Formulation of Business Strategy in 3D Printing Business - Ellyahart, Ahmad Taufik; Hussein, Ananda Sabil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Business model canvas is a method applied to plan, illustrate, and analyze the business model of a company. This instrument was developed by Alexander Osterwalder and Yves Pigneur and has become an essential part of a methodology known as Lean Startup or Business Design Thinking. Meratus Utama is a company whose main business is printing, especially the 3D. However, poor strategic planning and hindrance in conducting efficient production processes have caused hindrances. In order to address this problem, the Business Model Canvas was used, followed by the application of Future Business Model Canvas, whose analysis results were used to create a business plan as an alternative for the business development of Meratus Utama. This study finds that the problems faced by the company is poor innovation and low machinery output, which limited its production capacity. Therefore, the appropriate strategy for the company is product development particularly by adding new features, upgrading the quality, utilizing new technologies to create excellent products, increasing the number of employees, and investing in machinery.